Pain after Arteriovenous Access Creation. Issue 4 (April 2022) - Howk, Amy; McAdams, Callie; Heidel, Eric; Grandas, Oscar
Abstract : Opioid exposure and addiction are a public health concern for all patients, particularly patients undergoing surgical procedures. Patients with end-stage renal disease are particularly vulnerable because of the large numbers of surgeries required to create and maintain hemodialysis access. This prospective cohort study evaluates the use of regional anesthesia compared to general anesthesia during hemodialysis access surgeries and its effect on postoperative opioid use. Abstract: Objectives: Dialysis access creation is a common outpatient procedure that can be completed using general, regional, or local anesthetic techniques. There are few endorsed guidelines regarding opioid-based pain control following fistula creation. The purpose of this study was to determine whether utilization of regional anesthesia (RA) is associated with the decreased use of narcotics postoperatively. Methods: We performed a prospective cohort study including all patients undergoing arteriovenous fistula creation with one vascular surgeon from August 2019 to February 2020. Patients were selected for regional versus general anesthesia. Selection for anesthesia type was determined by the primary anesthesiologist. Patients selected for RA underwent supraclavicular brachial plexus block with 30 cm 3 of 0.5% ropivacaine. Patients were seen in clinic follow-up and completed a questionnaire regarding their postoperative opiate use and pain control. Results: In the study period, 52 patients underwent arteriovenous fistula creation and completed the follow-up questionnaire. Forty patients received RA. Seventy-five percent of patients sent home with a narcotic prescription filled the prescription. There was a significant difference in postoperative opioid use between the two study groups. Patients who received regional block took on average 3.3 pills totaling 16.5 morphine milligram equivalents, whereas patients who received general anesthesia took on average 6.64 pills totaling 33.2 morphine milligram equivalents ( P = 0.04). Conclusions: Morbidity and mortality related to opiate use continues to be a public health issue in the United States. This study demonstrates that regional anesthetic techniques in comparison to general anesthesia can result in a significant decrease in postoperative opiate consumption.